2015
DOI: 10.1093/mnras/stv738
|View full text |Cite
|
Sign up to set email alerts
|

The thermal emission from boulders on (25143) Itokawa and general implications for the YORP effect

Abstract: Infrared radiation emitted from an asteroid surface causes a torque that can significantly affect rotational state of the asteroid. The influence of small topographic features on this phenomenon, called the YORP effect, seems to be of utmost importance. In this work, we show that a lateral heat diffusion in boulders of suitable sizes leads to an emergence of a local YORP effect which magnitude is comparable to the YORP effect due to the global shape. We solve a three-dimensional heat diffusion equation in a bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Additionally, Lowry et al (2014) analysed implications of the detected YORP effect for Itokawa by using a detailed thermophysical model and concluded that the asteroid consists of two very different parts: (i) the main body with the density '1.75 g/cm 3 and (ii) the head with the density '2.85 g/cm 3 . While this striking difference may be in part due to their model incompleteness (e.g., Golubov et al, 2014;Ševeček et al, 2015), the two values again roughly bracket the expected interval of Apophis bulk density. We thus use the same bulk-density distribution function as shown in Fig.…”
Section: Statistical Distribution Of Semimajor Axis Changementioning
confidence: 62%
“…Additionally, Lowry et al (2014) analysed implications of the detected YORP effect for Itokawa by using a detailed thermophysical model and concluded that the asteroid consists of two very different parts: (i) the main body with the density '1.75 g/cm 3 and (ii) the head with the density '2.85 g/cm 3 . While this striking difference may be in part due to their model incompleteness (e.g., Golubov et al, 2014;Ševeček et al, 2015), the two values again roughly bracket the expected interval of Apophis bulk density. We thus use the same bulk-density distribution function as shown in Fig.…”
Section: Statistical Distribution Of Semimajor Axis Changementioning
confidence: 62%
“…The shape and surface properties of Arrokoth and any obliquity variations could change the strength and sign of the YORP torques (79)(80)(81)(82). Also, both YORP torques perpendicular to the spin axis and BYORP torques perpendicular to the orbit normal vector are minimized at high obliquities and binary inclinations, respectively (76, 81).…”
Section: Binary Merger Mechanismsmentioning
confidence: 99%
“…Clearly, if the collective crosssection of such surface features is large, details of conduction across them may have significant consequences. Ideally, the situation calls for a complete 3D heat transfer model (e.g., Golubov et al, 2014;Ševeček et al, 2015). Importantly, these studies indicate an overall tendency for YORP to spin objects up.…”
Section: Frontiers In Modeling Effortsmentioning
confidence: 85%
“…A surface boulder can give an object a locally small radius of curvature and 3D effects may become important. Full 3D conduction is computationally expensive (e.g., Golubov et al, 2014;Ševeček et al, 2015), but the potential consequences are significant. In this case, a general finite-element method is used to solve the heat diffusion problem.…”
Section: Frontiers In Modeling Effortsmentioning
confidence: 99%

The Yarkovsky and YORP Effects

Vokrouhlicky,
Bottke,
Chesley
et al. 2015
Preprint